2020
DOI: 10.1002/pi.6148
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecules of the cell: a polymer science viewpoint

Abstract: Polyelectrolytes are ubiquitous in biology, from the polynucleotide chain in our DNA, the hyaluronic acid in the vitreous body of the eye (Gao et al., Int J Ophthalmol, 8, 437-440, 2015) to the myosin and actin fibrils that make up our muscles. While synthetic polyelectrolytes are well studied, their correlation to biological polyelectrolytes is just beginning. This review will examine the polyelectrolytes that make up fundamental cell biology from a macromolecular perspective and the implications polyelectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The qualitative similarity in response of the resting potential in living cells ( Figure 5 d) and the degree of swelling in polyelectrolyte gels ( Figure 1 ) to the ratio of mono- to divalent cation concentration led to the conjecture that polyelectrolyte gels might play an important role in the measured resting potential [ 6 , 72 , 73 ]. Indeed, an electric potential difference is associated with polyelectrolytes ( Section 2.3 ), and the intracellular milieu is abundant with charged polymers, for example, cytoskeletal filaments [ 74 ]. Experiments focusing on the cortical layer, which is made of cytoskeletal filaments and is located below and adjacent to the lipid membrane indicated that structural changes in the layer were coupled to transient changes in the electric potential difference [ 75 ].…”
Section: Evidence Of Ion-induced Abrupt Transition In Biological Smentioning
confidence: 99%
“…The qualitative similarity in response of the resting potential in living cells ( Figure 5 d) and the degree of swelling in polyelectrolyte gels ( Figure 1 ) to the ratio of mono- to divalent cation concentration led to the conjecture that polyelectrolyte gels might play an important role in the measured resting potential [ 6 , 72 , 73 ]. Indeed, an electric potential difference is associated with polyelectrolytes ( Section 2.3 ), and the intracellular milieu is abundant with charged polymers, for example, cytoskeletal filaments [ 74 ]. Experiments focusing on the cortical layer, which is made of cytoskeletal filaments and is located below and adjacent to the lipid membrane indicated that structural changes in the layer were coupled to transient changes in the electric potential difference [ 75 ].…”
Section: Evidence Of Ion-induced Abrupt Transition In Biological Smentioning
confidence: 99%
“…The convergence of biological sciences with macromolecular design will continue to enable new directions, and Kozawa et al describe the structure of a biological cell using macromolecular terminology and perspective. 1 Kordbacheh et al further exploit nature's building blocks with a discussion of protein and peptide design with novel functionalization strategies, thus potentially encoding morphology and performance. 2 Henderson et al highlight the importance of supramolecular synthetic pathways, asking molecular structure to assemble and provide unprecedented control of molecular shape and functionality with exquisite precision.…”
mentioning
confidence: 99%